Evaluation of standardized automated rapid antimicrobial susceptibility testing of Enterobacterales-containing blood cultures: a proof-of-principle study. (7th August 2020) - Mancini, Stefano; Bodendoerfer, Elias; Kolensnik-Goldmann, Natalia; Herren, Sebastian; Röthlin, Kim; Courvalin, Patrice; Böttger, Erik C
Abstract: Background: Rapid antimicrobial susceptibility testing (RAST) of bacteria causing bloodstream infections is critical for implementation of appropriate antibiotic regimens. Objectives: We have established a procedure to prepare standardized bacterial inocula for Enterobacterales-containing clinical blood cultures and assessed antimicrobial susceptibility testing (AST) data generated with the WASPLab TM automated reading system. Methods: A total of 258 blood cultures containing Enterobacterales were examined. Bacteria were enumerated by flow cytometry using the UF-4000 system and adjusted to an inoculum of 10 6  cfu/mL. Disc diffusion plates were automatically streaked, incubated for 6, 8 and 18 h and imaged using the fully automated WASPLab TM system. Growth inhibition zones were compared with those obtained with inocula prepared from primary subcultures following the EUCAST standard method. Due to time-dependent variations of the inhibition zone diameters, early AST readings were interpreted using time-adjusted tentative breakpoints and areas of technical uncertainty. Results and conclusions: Inhibition zones obtained after 18 h incubation using an inoculum of 10 6  cfu/mL prepared directly from blood cultures were highly concordant with those of the EUCAST standard method based on primary subcultures, with categorical agreement (CA) of 95.8%. After 6 and 8 h incubation, 89.5% and 93.0% of the isolates produced interpretable results, respectively, with CA of >98.5% and very low numbers of clinical categorization errors for both the 6 h and 8 h readings. Overall, with the standardized and automated RAST method, consistent AST data from blood cultures containing Enterobacterales can be generated after 6–8 h of incubation and subsequently confirmed by standard reading of the same plate after 18 h.